Sudut Ilmu Sebagai Upaya Meningkatkan Minat Baca di SDN Kejagan, Kecamatan Trowulan, Mojokerto - Yanda Bara Kusuma; Febi Nour Amaliah; Roiisul Ibaad Aunillah; Bimo Putro Nusuantoro; Muhammad Gilang Zain Assalam; Zumrotul Rosyidah; Ika Yuliana Wati; Nursinta Abadiyah; Ifthar Ramadhana Wahyudi; Agustin Nur Awaliyah; Davina Nasywa Ardelia (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This study aims to increase the reading interest of students at SDN Kejagan in Trowulan District, Mojokerto. Based on library visit data in April 2024, it was recorded that the level of visits was very low, especially in the upper classes. The "Knowledge Corner" program was initiated by KKN-T Bela Negara students as an effort to increase students' literacy interest. This study uses a qualitative method with a descriptive approach. Data were obtained through interviews, observations, and questionnaires of grade 3 students, as well as secondary data from the library. The results of the study showed that the low reading interest was caused by inadequate library facilities and reading habits that had not yet formed. The implementation of the "Knowledge Corner" program includes preparing library decorations, implementing interactive literacy activities, and further evaluation. This program has succeeded in increasing students' enthusiasm for literacy activities, which is expected to have a positive impact on reading interest and visits to the library. The implications of this study emphasize the importance of the role of teachers and library managers in creating an environment conducive to reading and sustainable literacy.